To apply the properties of integer exponents, we can rewrite the expression as:
(14^3 * 27^(-7))^(1/3)^4
Now, let's simplify each term separately:
14^3 = 14 * 14 * 14 = 2,744
27^(-7) = 1/(27^7)
Now, let's simplify the expression further:
(2,744 * (1/(27^7)))^(1/3)^4
(2,744 * (1/823543))^(1/3)^4
Now, let's simplify the term in brackets:
(2,744/823543)^(1/3)^4
Now, let's simplify the exponent:
(2,744/823543)^(4/3)
To simplify the expression further, we can take the cube root of both the numerator and the denominator:
(14/27)^(4/3)
To simplify the exponent further, we can expand it as a fractional exponent:
(14/27)^(4/3) = ((14)^(4/3))/(27^(4/3))
Now, let's simplify each term separately:
(14)^(4/3) = (14^4)^(1/3) = 38416^(1/3) = 46
(27)^(4/3) = (27^4)^(1/3) = 531441^(1/3) = 81
Now, let's substitute these values back into the expression:
((14)^(4/3))/(27^(4/3)) = 46/81
Therefore, the simplified fraction is 46/81.
Apply the Properties of Integer Exponents to generate equivalent expressions to (14^3⋅27^−7)^0\3^4 with only positive exponents, then solve the expression. Your answer will be a simplified fraction with no remaining exponents.(1 point)
(14^3⋅27^−7)^0\3^4=
1 answer